Diversity in information technology education issues and controversies - Trajkovski, Goran, 1972- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"This book investigates the status of diversity in the field of IT education with research on racial, gender, national origin, disability and other diversity categories"--Provided by publisher.